Kolaborasi Mahasiswa KKN dan Masyarakat dalam Perayaan HUT RI dan HUT Desa Cimanggu: Strategi Penguatan Solidaritas Sosial dan Budaya Lokal - Cece Suhendi; Eri Sri Wahiddah; Mellyawati Intania Zahara; Yollanda Ayu Rengganis; Russy Marwa Rusefa; Syahid Akbar Almunawar (Jurnal Pengabdian West Science, 2026)
The celebration of Indonesia’s Independence Day (HUT RI) and the Village Anniversary (HUT Desa) plays a crucial role in strengthening social solidarity and local identity. The Community Service Program (KKN) in Cimanggu Village, Palabuhanratu District, Sukabumi Regency, from July 29 to September 4, 2024, facilitated collaboration between 19 university students and local residents to successfully hold these events. A participatory approach was em (Muliyana, et al., 2025)ployed through planning, implementation, and evaluation stages. Data were collected via observation, interviews, and documentation. The results show a ±45% increase in community participation compared to the previous year, intergenerational engagement, and strengthened communal bonds. For students, the program enhanced communication, leadership skills, and cultural understanding. This activity demonstrates that culture-based collaboration can be an effective strategy for building social capital and preserving local wisdom.